Bioinspired Phototropic MXene‐Reinforced Soft Tubular Actuators for Omnidirectional Light‐Tracking and Adaptive Photovoltaics. (3rd March 2022) - Yang, Mengyuan; Xu, Yiyi; Zhang, Xuan; Bisoyi, Hari Krishna; Xue, Pan; Yang, Yanzhao; Yang, Xiao; Valenzuela, Cristian; Chen, Yuanhao; Wang, Ling; Feng, Wei; Li, Quan
Abstract: Endowing artificial advanced materials and systems with biomimetic self‐regulatory intelligence is of paramount significance for the development of somatosensory soft robotics and adaptive optoelectronics. Herein, a bioinspired phototropic MXene‐reinforced soft tubular actuator is reported that exhibits omnidirectional self‐orienting ability and is capable of quickly sensing, continuously tracking, and adaptively interacting with incident light in all zenithal and azimuthal angles of 3D space. The novelty of the soft tubular actuator lies in three aspects: 1) the new polymerizable MXene nanomonomer shows high compatibility with liquid crystal elastomer (LCE) matrices and can be in situ photopolymerized into the polymer networks, thus enhancing the mechanical and photoactuation properties; 2) the distinct hollow and radially symmetrical structure facilitates the actuator with fast photoresponsiveness and phototropic performance through retarding the heat conduction along the radial direction; 3) the MXene‐LCE soft tubular actuator simultaneously integrates sensing, actuation, and built‐in feedback loop, thus leading to a high light‐tracking accuracy and adaptive phototropism like a hollow stem of plants in nature. As a proof‐of‐concept demonstration, an adaptive photovoltaic system with solar energy harvesting maximization is illustrated. This work can provide insights into the development of artificial intelligent materials toward adaptive optoelectronics, intelligent soft robotics, and beyond. Abstract : Bioinspired MXene‐reinforced soft tubular actuators with omnidirectional light‐tracking and adaptive phototropism are demonstrated through in situ photopolymerization of a judiciously designed photopolymerizable MXene nanomonomer into reversible shape‐morphing crosslinked main‐chain liquid crystal elastomers. Like the hollow stem of plants, the resulting actuators show a high light‐tracking accuracy and are capable of quickly sensing, continuously tracking, and adaptively interacting with the incident light in all zenithal and azimuthal angles of 3D space.